2011
DOI: 10.1016/j.biopsych.2010.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Forethought: Delayed Reward Discounting Differentiates High- and Low-Lethality Suicide Attempts in Old Age

Abstract: Background-The decision to commit suicide may be impulsive, but lethal suicidal acts often involve planning and forethought. People who attempt suicide make disadvantageous decisions in other contexts, but nothing is known about the way they decide about the future. Can the willingness to postpone future gratification differentiate between individuals prone to serious, premeditated and less serious, unplanned suicidal acts?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
126
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 43 publications
17
126
0
3
Order By: Relevance
“…Our previous study (Takahashi et al, 2008b) demonstrated that depressive patients are more irrational in intertemporal choices for gain and loss than healthy controls. Also, a recent study reported that impulsive suicide attempters discount delayed rewards steeply (Dombrovski et al, 2011). These findings indicate that irrational suicidal behavior may be associated with large k values and smaller q values across gain and loss.…”
Section: Decision Over Time (Intertemporal Choice)mentioning
confidence: 82%
“…Our previous study (Takahashi et al, 2008b) demonstrated that depressive patients are more irrational in intertemporal choices for gain and loss than healthy controls. Also, a recent study reported that impulsive suicide attempters discount delayed rewards steeply (Dombrovski et al, 2011). These findings indicate that irrational suicidal behavior may be associated with large k values and smaller q values across gain and loss.…”
Section: Decision Over Time (Intertemporal Choice)mentioning
confidence: 82%
“…Cognitive control can be thought of as the ability to organize information in a way that helps achieve the best outcome. It underlies certain (but not all) aspects of decision-making, which in turn appears impaired in younger (Jollant et al, 2005) and older (Dombrovski et al, 2010, Dombrovski et al, 2011a suicide attempters. Decisions that involve uncertainty, options with multiple features, and changes over time place particularly high demands on cognitive control (Dombrovski et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…Ce résultat a été répliqué depuis chez des adolescents (Dougherty et al, 2009 ;Mathias et al, 2011) Il a aussi été mis en évidence une prise de décision désavantageu-se chez le sujet âgé suicidant (Clark et al, 2011, Dombrovski et al, 2011b, suggérant que les anomalies de prise de décision peuvent être un facteur cognitif de vulnérabilité suicidaire à tout âge.…”
Section: La Prise De Décisionunclassified